On evaluation of completeness and consistency of non-functional requirements - Paškevičiūtė, Lina; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2004)
The paper proposes how to improve SIG graph approach used in NFR framework of Toronto group in order to evaluate consistency of NFR and completeness of operationalisation. The proposed approach extends the set of labels using to mark SIG softgoals and introduces weights for calculating measures of NFR consistency and completeness of operationalisation.
Keywords: requirements engineering; non-functional requirements; requirements completness; requirements consistency